Dishonest Newton Method Applied in Continuation Power Flow Through a Geometric Parameterization Technique - Bonini Neto, A. [UNESP]; Magalhaes, E. M. [UNESP]; Alves, D. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
The electricity sector has gone through several transformations due primarily to increased electricity demand, especially in emerging countries. This encourages more investment in the generation and leads to a growing concern about the development and improvement of static voltage stability tools of power systems. This paper presents a geometric parameterization technique for continuation power flow based on the addition of a line which passes through of points in the plane formed by the variables of voltage magnitude or voltage angle and loading factor. This technique eliminates the Jacobian matrix singularity at the maximum loading point, which allows obtaining the solution trajectory (P-V curve) without any need to change the parameter, which is a very common procedure in the continuation power flow currently available. This paper also investigates the influence of updating the modified Jacobian matrix only when the system undergoing significant change (Dishonest Newton Method), rather than update it every iteration. The results show a reduction of the CPU time in tracing of P-V curve.
Keywords: Continuation power flow; Jacobian matrix; Maximum loading point; P-V curve; Parameterization technique